Reverberations in the Torrens system: a new Land Transfer Act in New Zealand. Issue 2 (8th July 2019) - Toomey, Elizabeth
Abstract : Purpose: On 12 November 2018, New Zealand's Land Transfer Act 2017 came into force. The purpose of this paper is to pinpoint some of the significant changes in the Act that challenge the fundamental concepts of the Torrens system of registration. Design/methodology/approach: The paper addresses three significant reforms: a definition of land transfer fraud; the concept of immediate indefeasibility with limited judicial discretion and its impact on volunteers and the Gibbs v. Messer anomaly; and the compensation regime. Case studies illustrate the effect of these changes. Findings: The limited legislative definition of fraud reflects the common law and allows for any necessary flexibility. The new Act reiterates the principle of immediate indefeasibility but qualifies it with the introduction of some judicial discretion. This is a novel concept for the courts and will undoubtedly be dealt with cautiously. The author voices some disquiet with regard to some of the guidelines set out in s 55(4) of the Act. The compensation provisions introduce an element of an owner's culpability. An owner now runs the risk of reduced compensation if there has been a lack of proper care. Research limitations/implications: The implications of this research are fundamental for New Zealand's land transfer system. Practical implications: The limited judicial discretion will challenge the courts of New Zealand. The new compensation provisions will ensure that an owner's carelessness will be accountable. Originality/value: This study is one of the first to analyse the Land Transfer Act 2017 (New Zealand). Its value extends beyond New Zealand shores as it has implications for global land transfer systems.